2014
DOI: 10.1007/s10928-014-9349-1
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antibody disposition: a simplified PBPK model and its implications for the derivation and interpretation of classical compartment models

Abstract: The structure, interpretation and parameterization of classical compartment models as well as physiologically-based pharmacokinetic (PBPK) models for monoclonal antibody (mAb) disposition are very diverse, with no apparent consensus. In addition, there is a remarkable discrepancy between the simplicity of experimental plasma and tissue profiles and the complexity of published PBPK models. We present a simplified PBPK model based on an extravasation rate-limited tissue model with elimination potentially occurri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 35 publications
2
32
0
Order By: Relevance
“…Because, theoretically, all chimeric, humanized and human monoclonal antibodies are similar to endogenous IgG, important differences are observed between antibodies and diseases, which are due, at least in part, to target antigen mass. Structural pharmacokinetic model describing antibodies is bicompartimental [6,171], and target-mediated drug disposition (TMDD) models are used to describe antibody and target joint kinetics.…”
Section: Antigenic Targets Present In Several Tissuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Because, theoretically, all chimeric, humanized and human monoclonal antibodies are similar to endogenous IgG, important differences are observed between antibodies and diseases, which are due, at least in part, to target antigen mass. Structural pharmacokinetic model describing antibodies is bicompartimental [6,171], and target-mediated drug disposition (TMDD) models are used to describe antibody and target joint kinetics.…”
Section: Antigenic Targets Present In Several Tissuesmentioning
confidence: 99%
“…[1][2][3][4][5] The pharmacokinetics of mAbs is usually described using 2-compartment models with first-order transfer rates. [6] Central and steady-state volumes of distribution of mAbs are usually 3-5 L and 5-15 L [1,2,4] , respectively, values which suggest that mAbs are confined to lymphatic and blood vessels, and exhibit low (but not inexistent) tissue penetration. The elimination of IgG involves two different pathways.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of target antigenic mass is described in Sect. 3.2.2 [28]. More specifically, two-compartment models were used to describe the pharmacokinetics of infliximab [29], rituximab [30], adalimumab [31,32], golimumab [33], and tocilizumab in RA [34,35].…”
Section: Pharmacokinetics Of Mabs Used In Ramentioning
confidence: 99%
“…Therefore, the common interpretation for IgG low volumes of distribution being essentially confined inside blood and interstitial tissues may be abusive. Indeed, a recent study used physiologically based pharmacokinetics and suggested that, central and peripheral compartments of twocompartment models may not be considered as blood and interstitial spaces, respectively, but rather as two distinct groups of tissues, some being kinetically similar to plasma and others not [28]. In addition, non-specific elimination may concern not only unbound antibodies, but also antibody-target complexes.…”
Section: Distributionmentioning
confidence: 99%
“…The concept of minimal PBPK models is not novel and "hybrid PBPK models" (13,14) or minimal PBPK models (12) have been used to describe the disposition of small chemical molecules. These concepts have been recently extended to the modelling of mAbs for mice (15) and for both mice and humans (12,16), but FcRn-mediated distribution and elimination are not explicitly taken account of in these minimal versions of PBPK model for mAbs.…”
Section: Introductionmentioning
confidence: 99%